How do different brands of size 1 laryngeal mask airway compare with face mask ventilation in a dedicated laryngeal mask airway teaching manikin?. Issue 3 (11th August 2017) - Tracy, Mark Brian; Priyadarshi, Archana; Goel, Dimple; Lowe, Krista; Huvanandana, Jacqueline; Hinder, Murray
Abstract : Background: International neonatal resuscitation guidelines recommend the use of laryngeal mask airway (LMA) with newborn infants (≥34 weeks' gestation or >2 kg weight) when bag-mask ventilation (BMV) or tracheal intubation is unsuccessful. Previous publications do not allow broad LMA device comparison. Objective: To compare delivered ventilation of seven brands of size 1 LMA devices with two brands of face mask using self-inflating bag (SIB). Design: 40 experienced neonatal staff provided inflation cycles using SIB with positive end expiratory pressure (PEEP) (5 cmH2 O) to a specialised newborn/infant training manikin randomised for each LMA and face mask. All subjects received prior education in LMA insertion and BMV. Results: 12 415 recorded inflations for LMAs and face masks were analysed. Leak detected was lowest with i-gel brand, with a mean of 5.7% compared with face mask (triangular 42.7, round 35.7) and other LMAs (45.5–65.4) (p<0.001). Peak inspiratory pressure was higher with i-gel, with a mean of 28.9 cmH2 O compared with face mask (triangular 22.8, round 25.8) and other LMAs (14.3–22.0) (p<0.001). PEEP was higher with i-gel, with a mean of 5.1 cmH2 O compared with face mask (triangular 3.0, round 3.6) and other LMAs (0.6–2.6) (p<0.001). In contrast to other LMAs examined, i-gel had no insertion failures and all users found i-gel easy to use. Conclusion: This study has shown dramatic performance differences in delivered ventilation, mask leak and ease of use among seven different brands of LMA tested in a manikin model. This coupled with no partial or complete insertion failures and ease of use suggests i-gel LMA may have an expanded role with newborn resuscitation as a primary resuscitation device.